2017
DOI: 10.1116/1.4978871
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of immobilized epidermal growth factor: Covalent versus noncovalent grafting

Abstract: In an effort to rationalize and optimize an antiapoptotic coating combining chondroitin sulfate (CS) and epidermal growth factor (EGF) for vascular applications, the authors here report the comparison of two grafting strategies aiming to display EGF in an oriented fashion on CS. For that purpose, the authors produced, purified, and characterized a chimeric protein corresponding to EGF that was N-terminally fused to a cysteine and a coil peptide. The chimera was covalently immobilized via its free thiol group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In general, this technique involves the reaction of free thiols in the GF with thiol-reactive groups in the substrate surface. In GFs, free thiol groups exist in cysteine residues, but may also be introduced chemically or with recombinant technology (Place et al, 2012;Chen et al, 2014;Riahi et al, 2017). Functionalized GFs react with free thiols on the substrate surface, leading to their immobilization.…”
Section: Thiol Coupling Immobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, this technique involves the reaction of free thiols in the GF with thiol-reactive groups in the substrate surface. In GFs, free thiol groups exist in cysteine residues, but may also be introduced chemically or with recombinant technology (Place et al, 2012;Chen et al, 2014;Riahi et al, 2017). Functionalized GFs react with free thiols on the substrate surface, leading to their immobilization.…”
Section: Thiol Coupling Immobilizationmentioning
confidence: 99%
“…Due to their highly specific and stable interaction, coiledcoil structures have been used in various biomedical and biotechnological applications, including GF immobilization (Boucher et al, 2008(Boucher et al, , 2010Apostolovic et al, 2010;Murschel et al, 2013;Assal et al, 2015;Noel et al, 2016;Riahi et al, 2017). The target GF is expressed as a fusion protein with one coiled-coil strand, while the substrate surface is functionalized with the complementary coiled-coil strand.…”
Section: Coiled-coil Interactionsmentioning
confidence: 99%
“…Moreover, the HAp-1:1 group showed high cysteine-knot stability through adsorption/desorption processes, indicating that nano-textured HAp surfaces can better incorporate BMP-2 molecules through adsorption and can aid in BMP-2 biological activity. Alginate microbeads were surface condensed with heparin through polyelectrolyte complexes (diethylaminoethyldextran (DEAE-D), poly-l-ornithine, and poly-l-arginine) to provide a delivery system for BMP-2 [128]. The authors observed distinct release profiles for each of the systems designed.…”
Section: Physical Adsorptionmentioning
confidence: 99%
“…To realize and optimize an antiapoptotic coating for vascular applications, EGF was combined with chondroitin sulfate. Riahi and Murschel designed and prepared a chimeric EGF in which the N-terminal was fused with a cysteine or coil-forming peptide. In the former case, the chimeric EGF was covalently tethered through the thiol group.…”
Section: Design Of Binding Growth Factormentioning
confidence: 99%